Anti-inflammatory and immunomodulating effects of clarithromycin in patients with cystic fibrosis lung disease - Alexander L. Pukhalsky; Galina V. Shmarina; Nikolai I. Kapranov; Svetlana N. Kokarovtseva; Daria Pukhalskaya; Natalia J. Kashirskaja (Hindawi Limited, 2004)
BACKGROUND and aim: Macrolide antibiotics are widely used in the treatment of suppurative lung diseases including cystic fibrosis (CF), the most common inherited fatal disease in the Caucasian population. This condition is characterized by secondary Pseudomonas infection resulting in neutrophil infiltration within the airways. The aim of the study was to investigate the evolution of inflammatory process in CF patients receiving long-term clarithromycin therapy.